Efforts Toward Elimination of Infectious Agents in Blood Products. (October 2018) - Jacquot, Cyril; Delaney, Meghan
The US blood supply has never been safer. This level of safety depends on a multifaceted approach including blood donor screening, sensitive infectious disease testing, and good manufacturing practice. However, risks remain for transfusion-transmitted infections due to bacterial contamination of platelets and emerging diseases. Thus, ongoing improvements in screening and testing are required. Newer pathogen reduction technologies have shown promise in further ameliorating the safety of the blood supply.